O001 Providing feedback and guidance on sleep perceptions using sleep wearables improves insomnia: Findings from the randomised Novel Insomnia Treatment Experiment ("NITE"). (9th November 2022) - Spina, M; Andrillon, T; Quin, N; Wiley, J; Rajaratnam, S; Bei, B
Abstract: Study Objectives: Insomnia is diagnosed based on self-reported sleep complaints. There are often differences between objectively recorded and self-reported sleep (sleep-wake state discrepancy), which is well-documented but not well understood. This two-arm, parallel-group, single-blind, superiority randomised controlled trial examined whether monitoring sleep using wearable sleep-measurement devices and providing feedback with support for helpful interpretation of objective sleep data improved insomnia symptoms. Methods: 113 (age M=47.53, SD=14.37, 64.9% female) individuals with insomnia symptoms (Insomnia Severity Index >= 10; ISI) from the community were randomised (permuted block randomization) to receive 5 weeks of (a) Feedback (n=57): feedback about objectively recorded sleep (actigraphy and optional EEG headband) with guidance for data interpretation and ongoing monitoring; (b) No-Feedback (n=56): sleep hygiene. Both conditions received one individual session and two check-in calls. The ISI (primary outcome), PROMIS Sleep Disturbance (SD), Sleep-Related Impairment (SRI), Depression, and Anxiety were assessed at baseline and post-intervention. Results: 103 (91.2%) participants completed the study. Preliminary intention-to-treat multiple regression showed that after controlling for baseline symptoms, the Feedback condition (n=52) had lower ISI (p=.0069, d=0.53) and SD (p=.033, d=0.38), but differences in SRI, Depression and Anxiety were not meaningful (p-values>.37) compared to No-Feedback condition (n=51). Conclusion: Providing feedback and guidance about objectively recorded sleep reduced insomnia severity and sleep disturbance in individuals with insomnia symptomology. With increasing access to wearable sleep-measurement devices, these findings explore how objective sleep measures, in combination with data interpretation guidance, could supplement and enhance current insomnia treatment. Australian New Zealand Clinical Trials Registry: ACTRN12619001636145.